Education in Emergencies: Concept and Applications - Takaeng, Chaleeya (Journal of Social Sciences Naresuan University, 2026)
This article explores the concept and application of Education in Emergencies (EiE), by adopting principles of EiE and the Inter-agency Network for Education in Emergencies Minimum Standards (INEE MS) as the analytical framework. The study highlights three domains, namely preparedness, response, and recovery, to examine mechanisms that safeguard the right to education, protect children, and provide psychosocial support during crises. A comparative review of case studies in Nepal, Pakistan, and Lebanon demonstrates that effective EiE requires strong collaboration at multiple levels and curricula adapted to post-crisis contexts to ensure safe and continuous learning. In Thailand, education policies do not explicitly adopt EiE but show partial alignment with INEE MS, particularly in child’s rights to education access and child protection. Nonetheless, key challenges remain. Legal restrictions, including the Immigration Act and national security regulations, restrict the mobility of displaced and stateless children, which affect their rights to education. Centralized governance, limited coordination mechanisms, inadequate teacher preparation, and the absence of systematic psychosocial support further constrain effective implementation. The analysis concludes that Thailand must strengthen its approach by embedding EiE principles more comprehensively. Incorporating INEE MS into education plans, reforming restrictive laws, enhancing teacher training, and integrating psychosocial dimensions are critical to building resilience and ensuring that no child is excluded from education in times of crisis.